The clinical characteristics and neurodevelopmental outcome of preterm infants with persistent periventricular echogenicity - Mi Hye Bae; Hyun Ji Jang; Na Rae Lee; Young Mi Han; Shin Yun Byun; Kyung Hee Park (Pediatrics and Neonatology)
Purpose: Periventricular echogenicity (PVE) presents as diffuse echo dense lesions of the periventricular white matter on cranial ultrasonography. Beyond two weeks of life, it is considered as prolonged or persistent PVE. The aim of our study was to investigate the clinical characteristics of preterm infants with persistent PVE beyond 2 weeks after birth and to determine whether these infants had an adverse neurodevelopmental outcome. Methods: The medical records of preterm infants who were born at < 34 weeks of gestation and admitted to Pusan National University Hospital between 2009 and 2014 were reviewed. A total of 28 preterm infants with persistent PVE were enrolled. Sixty compatible infants closely matched for gestational age and birth weight to infants with PVE were selected as the control group. Clinical data, including maternal, perinatal and neonatal characteristics, were analyzed. We compared the Bayley Scales of Infant Development-III at 12 months' corrected age. Results: The mean gestational age and birth weight were 31 + 3 (range, 29 + 2–33 + 6) weeks and 1523 (range, 911–2210) g, respectively, in the persistent PVE group. In the control group, the mean gestational age was 31 + 4 (range, 29 + 2–33 + 6) weeks and the mean birth weight was 1537 (range, 840–2100) g. There was no significant difference between the persistent PVE group and the control group, except for a significantly higher incidence of late sepsis in the persistent PVE group (p = 0.001). The results of Bayley test at 12 months of corrected age were available for 24 infants in the persistent PVE group and for 26 infants in the control group. A motor score of 86 (range, 78–95) versus 88 (range, 79–100), a language composite score of 88 (range, 78–97) versus 89 (range, 80–105), and a cognitive score of 90 (range, 81–100) versus 92 (range, 85–105) were observed in the persistent PVE group and the control group, respectively. No difference was detected in any scores between the two groups. Conclusion: The clinical characteristics and neurodevelopmental outcomes of preterm infants with persistent PVE were not different from those of infants with normal findings. Our study supports the concept that persistent PVE without cystic change may be a benign finding. Key Words: infant, leukomalacia, periventricular, premature